2015
DOI: 10.1002/chem.201503000
|View full text |Cite
|
Sign up to set email alerts
|

Normal‐to‐Abnormal NHC Rearrangement of AlIII, GaIII, and InIII Trialkyl Complexes: Scope, Mechanism, Reactivity Studies, and H2 Activation

Abstract: The present contribution reports experimental and theoretical mechanistic investigations on a normal-to-abnormal (C2-to-C4-bonded) NHC rearrangement processes occurring with bulky group 13 metal NHC adducts, including the scope of such a reactivity for Al compounds. The sterically congested adducts (nItBu)MMe3 (nItBu=1,3-di-tert-butylimidazol-2-ylidene; M=Al, Ga, In; 1 a-c) readily rearrange to quantitatively afford the corresponding C4-bonded complexes (aItBu)MMe3 (4 a-c), a reaction that may be promoted by T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 92 publications
4
58
0
Order By: Relevance
“…The NMR data for 1 and 2 are consistent with the coordination of IPr* to the M(III) centers. In particular, the 13 As determined through X-ray crystallographic studies (XRD), the solid-state molecular structure of 2 confirmed the effective coordination of IPr* to InMe3, resulting in a four-coordinate In(III) adopting a distorted tetrahedral geometry and coplanar to the NHC heterocyclic ring (Figure 2). The In-Ccarbene bond distance (2.330(5) Å) in 2 is a bit longer than those in (IMes)InMe3 and (IPr)InMe3 (2.292(6) and 2.309(2) Å, respectively; IMes = 1,3-bis(2,4,6-trimethylphenyl)-1,3-dihydro-imidazol-2-ylidene; IPr = 1,3-bis{2,6-bis(1-methylethyl)phenyl})-1,3-dihydro-imidazol-2-ylidene), likely reflecting greater steric hindrance between the NHC and InMe3 in 2 [20,21].…”
Section: Adducts (Iprmentioning
confidence: 78%
See 4 more Smart Citations
“…The NMR data for 1 and 2 are consistent with the coordination of IPr* to the M(III) centers. In particular, the 13 As determined through X-ray crystallographic studies (XRD), the solid-state molecular structure of 2 confirmed the effective coordination of IPr* to InMe3, resulting in a four-coordinate In(III) adopting a distorted tetrahedral geometry and coplanar to the NHC heterocyclic ring (Figure 2). The In-Ccarbene bond distance (2.330(5) Å) in 2 is a bit longer than those in (IMes)InMe3 and (IPr)InMe3 (2.292(6) and 2.309(2) Å, respectively; IMes = 1,3-bis(2,4,6-trimethylphenyl)-1,3-dihydro-imidazol-2-ylidene; IPr = 1,3-bis{2,6-bis(1-methylethyl)phenyl})-1,3-dihydro-imidazol-2-ylidene), likely reflecting greater steric hindrance between the NHC and InMe3 in 2 [20,21].…”
Section: Adducts (Iprmentioning
confidence: 78%
“…While stable for days in benzene/toluene at room temperature (under inert atmosphere), they quickly decompose to unknown species in CH2Cl2 and THF at room temperature, in line with severely hindered Lewis pairs. The NMR data for 3 and 4 only display sharp resonances As earlier mentioned, the sterically hindered Lewis pairs (ItBu)MMe 3 (M = Ga, In) are unstable and rearrange to the corresponding C4-bonded isomers (aItBu)MMe 3 (Scheme 1) [12][13][14]. To avoid such isomerization, the backbone-saturated carbene StBu, prepared according to a known procedure [23], was coordinated to GaMe 3 and InMe 3 .…”
Section: Adducts (Stbu)mme3 (3 M = Ga; 4 M = In)mentioning
confidence: 97%
See 3 more Smart Citations